2014
DOI: 10.1177/1073858414543150
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Brain Injury

Abstract: It is estimated that 2% of the population from industrialized countries live with lifelong disabilities resulting from traumatic brain injury (TBI) and roughly one in four adults are unable to return to work 1 year after injury because of physical or mental disabilities. TBI is a significant public health issue that causes substantial physical and economical repercussions for the individual and society. Electronic databases (PubMed, Web of Science, Google Scholar) were searched with the keywords traumatic brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 80 publications
0
24
1
Order By: Relevance
“…Wide variations exist among victims of abuse in recovery trajectory following TBI, even after stratifying for severity of the initial event causing the injury. 40 This wide range of outcomes appears to be shaped by the form and activity of genes (referred to as genomics) that are associated with recovery. How well a person recovers from TBI is partially determined by the particular genetic variations present in that individual.…”
Section: Genomic Variations Affecting Outcomesmentioning
confidence: 99%
“…Wide variations exist among victims of abuse in recovery trajectory following TBI, even after stratifying for severity of the initial event causing the injury. 40 This wide range of outcomes appears to be shaped by the form and activity of genes (referred to as genomics) that are associated with recovery. How well a person recovers from TBI is partially determined by the particular genetic variations present in that individual.…”
Section: Genomic Variations Affecting Outcomesmentioning
confidence: 99%
“… 9 Recent studies indicated that genetic variants, such as the APOE polymorphism, may also contribute to the severity and outcome of TBI. 10 , 11 However, the results and conclusion of these studies are not consistent, and the relation between the APOE genotype and TBI recovery remains unclear, partly due to the variable methods and limited sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, human gene polymorphism analyses indicate that various inflammatory factors are increased after TBI27. Inflammation can occur due to activation of inflammatory cytokines, resulting in secondary damage to the brain which in turn leads to a decline in learning ability as well as reduced memory and cognitive function28.…”
Section: Discussionmentioning
confidence: 99%